2012
DOI: 10.1111/j.1365-3156.2012.02985.x
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in young children of rural Burkina Faso: comparison of survey data from 1999 with 2009

Abstract: Abstractobjective For measurement of progress towards the Millennium Development Goal (MDG) 1, reliable data on nutrition indicators of specific countries are essential. Malnutrition is also the main determinant for childhood mortality, which is addressed in MDG 4.methods In the health and demographic surveillance area of Kossi Province in north-western Burkina Faso, nutritional parameters were compared in two cohorts of young children of the same age range from eight villages. Surveys took place in June and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…; Asres & Eidelman ; Central Statistical Agency ; Beiersmann et al . ). One of the core indicators of IYCF is dietary diversity, which is a proxy for adequate micronutrient density of foods and liquids other than breast milk.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Asres & Eidelman ; Central Statistical Agency ; Beiersmann et al . ). One of the core indicators of IYCF is dietary diversity, which is a proxy for adequate micronutrient density of foods and liquids other than breast milk.…”
Section: Introductionmentioning
confidence: 97%
“…Since the early 2000s, infant and young child feeding (IYCF) has been issued as an essential element to improve growth of children (United Nations 2000;WHO 2000WHO , 2001WHO , 2002Nguyen et al 2011). Implementation of the guiding principles of IYCF is essential in developing countries where the consequences of children's malnutrition, such as stunting, underweight and wasting, are very prevalent (Michael 2006;Black et al 2008;UNICEF 2008;Shetty 2009;Willey et al 2009;Asres & Eidelman 2011;Central Statistical Agency 2011;Beiersmann et al 2012). One of the core indicators of IYCF is dietary diversity, which is a proxy for adequate micronutrient density of foods and liquids other than breast milk.…”
Section: Introductionmentioning
confidence: 99%
“…The An even stronger associations of survival with MUAC and MUAC with FCPI could be observed if MUAC measurements in our dataset were more equally distributed across seasons; in our data a relatively small number of MUAC measurements were made in the lean season (June -August), when household cereal stocks from the last harvest are running low and proportion of children with low MUAC tends to be higher than in other seasons (42,43).…”
Section: Discussionmentioning
confidence: 60%
“…Malnutrition has been identified as a major underlying cause of childhood mortality in SSA as well as in the Nouna study area . In the Nouna study area, anthropometric surveys have consistently shown that malnutrition remains highly prevalent in young children, and this was particularly pronounced in the Cisse village .…”
Section: Discussionmentioning
confidence: 89%